Characteristics, Treatment Patterns, Healthcare Resource Utilization, and Costs Among Patients with Multifocal Motor Neuropathy: A US Claims Database Cohort Study - Nikhil Khandelwal; Marie Sanchirico; Ade Ajibade; Kiraat Munshi; Michelle Vu; Nicole Engel-Nitz; Christina Steiger; Amy J Anderson; Chafic Karam (Journal of Health Economics and Outcomes Research, 2025)
# Background Multifocal motor neuropathy (MMN) is a rare, slowly progressive nerve disorder characterized by asymmetric limb weakness without sensory abnormalities. MMN is often misdiagnosed due to similarities in clinical symptoms with conditions including amyotrophic lateral sclerosis (ALS), making diagnosis and treatment challenging.